2002
DOI: 10.1029/2002gl014812
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric reactive chlorine and bromine at the Great Salt Lake, Utah

Abstract: The presence of chlorine radical species in the lower troposphere has been postulated, but only indirect evidence of its existence has been reported. We present the first direct spectroscopic observations of up to 15 ± 2 pmoles/mole‐air chlorine oxide (ClO) in the mid‐latitude boundary layer and confirm a previous discovery of the existence of bromine oxide (up to 6 ± 0.4 pmoles/mole‐air BrO). Our observations from October 2000 suggest that reactive halogens are mobilized from salt on the flats around the Grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
144
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(147 citation statements)
references
References 21 publications
3
144
0
Order By: Relevance
“…Large concentrations of bromine and iodine (up to 200 ppt of BrO -Tas et al, 2005, and up to 10 ppt of IO -Zingler and Platt, 2005) have been reported over the Dead Sea (Israel) causing O 3 as low as 2 ppb; however, observations in other locations have shown much lower values (e.g. 6 ppt of BrO and 15 ppt of ClO over the Great Salt Lake; Stutz et al, 2002). The database of observations is very sparse and shows large variability between different locations, suggesting that the local characteristics (e.g.…”
Section: P S Monks Et Al: Tropospheric Ozone and Its Precursorsmentioning
confidence: 99%
“…Large concentrations of bromine and iodine (up to 200 ppt of BrO -Tas et al, 2005, and up to 10 ppt of IO -Zingler and Platt, 2005) have been reported over the Dead Sea (Israel) causing O 3 as low as 2 ppb; however, observations in other locations have shown much lower values (e.g. 6 ppt of BrO and 15 ppt of ClO over the Great Salt Lake; Stutz et al, 2002). The database of observations is very sparse and shows large variability between different locations, suggesting that the local characteristics (e.g.…”
Section: P S Monks Et Al: Tropospheric Ozone and Its Precursorsmentioning
confidence: 99%
“…24). 60 The authors speculate that the chlorine has been mobilised by heterogeneous reactions from the high molality salt solutions or crystalline salt on the flats, this likely to be the by-product of the bromine explosion mechanism (cf. reaction (67) b) The HO 2 to OH ratio can be changed via reactions 65 and 66.…”
Section: Experimental Evidencementioning
confidence: 99%
“…The [X]/[XO] ratio is largely determined by a combination of the reactions (56), (57), (59), (60). At any given time ,0.1% for Cl, 0.1 to 1% for Br and several 10% for I will be present in the form of a halogen atom.…”
Section: Halogen Radicals (Xo Oxo)mentioning
confidence: 99%
See 1 more Smart Citation
“…von Glasow and Crutzen (2003) for an overview). BrO has been found in the boundary layer during polar ozone depletion events (ODEs) (Hausmann and Platt, 1994), over salt lakes Stutz et al, 2002;Hönninger et al, 2004), and in the marine boundary layer (MBL) (Leser et al, 2003;Saiz-Lopez et al, 2004) and also in volcanic plumes (Bobrowski et al (2003), N. Bobrowski, pers. comm.).…”
Section: Introductionmentioning
confidence: 99%